Pengembangan Bakso Daging Sapi dan Kerang Darah sebagai Camilan Sumber Protein dan Zinc untuk Anak Usia Sekolah: Development of Blood Clam Meatballs as a Snack as a Source of Protein and Zinc for School-Age Children - Annisa, Risva Fadhilah; Nasution, Zuraidah; Setiawan, Budi (Jurnal Ilmu Gizi dan Dietetik, 2024)
School-age children need adequate nutritional intake to support learning activities at school. Meatballs contain high protein and are quite popular among children in Indonesia. In addition to protein, micronutrients such as minerals must also be met. This study aimed to develop beef meatballs with blood cockle substitution as an alternative source of protein and zinc for school-age children. This study used a Completely Randomized Design (CRD) with four treatments (substitution of beef with blood clam as much as 0, 10, 20, 30%). Data from the physicochemical properties of blood clam meatballs were analyzed using the ANOVA test and continued with the Tukey test. The results showed that the substitution of beef with blood clam results in a significant difference (p<0.05) in organoleptic acceptance (color, aroma, texture, taste, aftertaste, overall acceptance) and zinc levels. The selected meatball was F2 with 10% blood clam substitution. F2 was chosen as the best formulation based on the results of organoleptic tests and analysis of nutrient content, especially protein and zinc. This formula produces meatballs with a protein content of 13.6 g/100 g, zinc 2.28 mg/100 g, and calcium 98.18 mg/100 g. The content of macronutrients and minerals, especially zinc, from the selected formula meets the nutrient contribution of one snack to the AKG of school-age children (7-9 and 10-12 years). The serving size of blood clam meatballs was determined to be 200 g or 10 pieces. This serving size has a contribution value of 12.06% (7-9 years), 9.95% (10-12 years boys), and 10.47% (10-12 years girls) to energy. Meatballs from this selected formula can also be claimed as a source of protein and zinc. The results of this study indicate that blood clams can be used as an alternative raw material in beef-based products to improve their nutritional profile.